ANALISIS PENERAPAN PRODUKSI BERSIH PADA BATIK PRINTING IKM BATIK PUSPA KENCANA LAWEYAN SURAKARTA - Bambang Suhardi, Pringgo Widyo Laksono, dan Nabila Nur Fadhilah (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
Cleaner production is a strategy to reduce environmental pollution and also reducing resources consumption. The aim of this research was to choose alternative solutions for the implementation of cleaner production in printed batik in Batik Puspa Kencana Small Medium Enterprise (SME) using Analytic Hierarchy Process (AHP) method. Printed batik production in Batik Puspa Kencana SME produces environmental waste in the form of over consumption of energy, water and raw materials; disposal of wastewater directly into the river; and the use of chemical dyes that are harmful to human health and the environment. Identification of the problem used Ergonomic Checklist for Cleaner Production, which consisted of energy usage in general, water usage in general, material and chemical substance usage in general, and also prevention of pollution and waste in general. Then, determination of the causes of the problem used Fishbone diagram and 5W1H Method (What, Where, Who, When, Why, and How), so obtained several alternative solutions. The next step wasAHP to determine and assess alternative solutions based on technical, economical and environmental aspects. The result shows that